Forget what you know - Dodd, Christina (HQN, 2023)
"A submerged car is pulled from the bottom of the lake. The driver has been shot in the back of the head and no other bodies are found. Only the legendary Dragon's Heart remains inside. When it rises to the surface, greedy collectors from around the world gather. They'll stop at nothing to gain possession of the priceless artifact. Only one person stands in their way... Zoe Phoenix remembers nothing about her early childhood; her mother's desire to leave those years behind never worried her...until she's almost killed in a hit and run and, days later, her mother disappears. Now Zoe fears her family secrets won't stay buried long. She has no idea who tried to murder her or why, but she's determined to unravel the dangerous truths of her past--before they claim her future"--